Library online database system for undergraduate students - Azlan, Nor Athira; Zulkifli, Zahidah; Mohammad Daud, Nur Hidayah; Samsuri, Suhaila; Md Ali, Asma; Hussin, Husnayati (informatics (India) Ltd., 2016)
The demand of the good quality of research especially in academic field rose the emerging of library online databases services nowadays. Most of the universities in Malaysia have subscribed the library online databases to provide students more opportunity to explore research resources not limited only in certain regions but throughout all countries around the world. The services are expected to give benefit to the postgraduate and undergraduate students for academic purposes. However, most of undergraduate students are not aware of the existence of library online databases services that universities provided. They also discouraged to use the services due to the difficulties they faced when they used the services. Methods/Statistical Analysis: Interviews and Quantitative Research (survey) have been used as data collection method. The stratified random sampling technique was used to collect data from undergraduate students with different countries, age, gender, courses and level of study from (Year 1 to Year 4). The sample is scattered throughout 16 faculties in International Islamic University Malaysia (IIUM). Findings: From the study, current issues and problems were identified, features of library online database systems were analyzed then selected to be adapted into the future development of library online database system in International Islamic University Malaysia, IIUM library. Application/Improvements: The study is able to enhance the current IIUM library online databases flows and processes. The features selected to be adapted in future